Role of Metoprolol Succinate in the Treatment of Heart Failure and Atrial Fibrillation: A Systematic Review. (March 2020) - Vinereanu, Dragos; Spinar, Jindrich; Pathak, Atul; Kozlowski, Dariusz
Abstract : Background: Beta-blockers are one of the most important classes of cardiovascular agents and have been considered a cornerstone therapy in heart diseases, such as heart failure (HF) and atrial fibrillation (AF). Among different beta-blockers, metoprolol is a selective beta1 -adrenergic antagonist, which has been extensively used since the 1970s. Areas of Uncertainty: Although current guidelines include recommendations for the use of controlled-release metoprolol succinate in specific HF and AF indications, and despite extensive clinical experience with metoprolol, comparative evidence on the use of metoprolol succinate compared with other beta-blockers in these indications is limited. Data Sources: We systematically reviewed the data from head-to-head studies directly comparing this compound with other beta-blockers in the treatment of HF or AF. Only clinical trials and observational studies were considered; no other limits were applied. The quality and relevance of retrieved articles were reviewed. Results: A total of 18 articles of the 353 articles identified were selected for inclusion; 12 HF articles and 6 for AF. Additional references were identified from the bibliographies of retrieved articles. The studies show that oral prophylaxis with an appropriate dose of metoprolol may reduce new incidents of AF in high-risk patients. Furthermore, metoprolol succinate is associated with significant mortality and morbidity benefits in the treatment of HF. Conclusions: Despite the introduction of newer beta-blockers with differing clinical characteristics since its introduction, metoprolol succinate remains a useful drug in both HF and AF.